Human capital, technological progress and industrial restructuring - Zhao, Kui; Zhang, Luyao (PloS one, 2025)
Human capital and technological progress drive industrial restructuring toward rationalization and advancement, clarifying their theoretical interaction and examining the influence mechanism based on China’s three major industries data from 2008 to 2022, employing the PVAR and Hansen threshold models. The study shows that: (1) technological progress and industrial restructuring are mutually causal, while technological progress and human capital, and human capital and industrial restructuring are not mutually causal. (2) Within the research cycle, human capital has a ‘fast then slow then smooth’ influence on industrial structural adjustment, while technological progress has a ‘V’ influence on industrial structural adjustment, and technological progress has a ‘U’ influence on human capital. (3) Human capital and technological progress have played a facilitating role in industrial structural adjustment. Technological progress serves as the threshold, resulting in a double threshold effect of human capital on industrial structure rationalization, a single threshold effect is observed in its advancement. The policy implications are as follows: first, accelerate the mechanism of industrial structure upgrading, and drive the quality improvement and structure optimization of industrial human capital; second, give full play to the iterative role of technological innovation, and build a ‘technology-capital’ complementary mechanism; third, ‘according to the time - according to the place - according to the production’, Integration of human capital, technological progress and industrial restructuring synergistic development paths.